Penerapan Model Pembelajaran Terpadu Terhadap Ketuntasan Hasil Belajar IPA SD - Muh. Amir Masruhim (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: This research is developmental research using Four D Model and it is applied to 40 elementary school students at Samarinda. The research developed learning material, included learning planning, worksheet, achievement test for science materials. The learning instrument were collected three times. The collected data were analyzed with descriptive analysis. Results found that students achievement individually were increase and students achievement classically got 89% in the first research and got 80% in the second research. Students responded to equipment learning generally.